Twenty-first-century readings of E.M. Forster's Maurice (Liverpool : Liverpool University Press, 2020)
This is the first book focused on Forster's Maurice and its legacies in modern and contemporary fiction, film and new media. Ground-breaking essays by leading scholars offer new readings by exploring overlooked contexts including: feminism and the 'social purity' movement; anti-Fascism; religion and allegory; and early twentieth-century contestations over body-soul relation.
Introduction: Maurice through Time -- I Forebears and Friends -- 1. 'An unspeakable of the Oscar Wilde sort': E.M. Forster, Maurice and the Legacy of Aestheticism -- 2. Women In and Out: Forster, Social Purity and Florence Barger -- 3. The Master and the Pupil: E.M. Forster, Christopher Isherwood and the Forging of a Queer Aesthetic -- II Contemporary Contexts -- 4. 'Flat pieces of cardboard stamped with a conventional design': Women and Narrative Exclusion in E.M Forster's Maurice -- 5. Maurice: Beyond Body and Soul -- 6. Maurice and Religion -- III Afterlives -- 7. 'A man embedded in society': Homosexuality and the 'Social Fabric' in Maurice and Hollinghurst's The -- 8. Sexuality, Allegory and Interpretation: E.M. Forster's Maurice and Damon Galgut's Arctic Summer -- 9. Maurice without Ending: From Forster's Palimpsest to Fan-Text -- Bibliography -- Notes on Contributors -- Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, viewed on May 01, 2020).
eBooks on EBSCOhost
Keywords: Forster, E. M. -- 1879-1970.; Forster, E. M. -- 1879-1970 -- Criticism and interpretation; Forster, E. M. -- 1879-1970; Electronic books; Criticism, interpretation, etc